External validation of a multi-institutional retroperitoneal sarcoma nomogram - Raut, Chandrajit P.; Hohenberger, Peter; Jakob, Jens (Cancer, 2016)
Background: A multi-institutional nomogram for predicting disease-free survival (DFS) and overall survival (OS) in patients with primary retroperitoneal sarcoma (RPS) incorporating relevant prognostic factors not included in the American Joint Committee on Cancer staging system for soft tissue sarcoma has been reported. The authors validated this nomogram with an independent, transatlantic cohort. Methods: Data from patients with RPS who were undergoing definitive resection at 1 of 6 sarcoma centers in Europe and North America (“validation set”) were used to validate a RPS nomogram developed from 3 other centers (“development set”). The nomogram incorporated 6 variables: age, tumor size, grade, histologic subtype, multifocality, and quality of surgery. Nomogram-predicted probabilities were stratified into 6 subgroups and compared with observed outcomes. Discriminative ability was quantified by Harrell C statistics. Results: The validation and development sets included 631 and 523 patients, respectively, all of whom underwent surgical resection at the institutions represented. The 7-year DFS and OS rates for the validation set were 38% (95% confidence interval, 34%-43%) and 58% (95% confidence interval, 53%-63%), respectively. All 6 nomogram variables were found to be independently prognostic. The corrected Harrell C statistics concordance index values for the validation set were 0.69 for DFS and 0.73 for OS, which were similar to those for the development set, suggesting good calibration of the nomogram in the validation cohort. Conclusions: The RPS nomogram was externally validated using a larger, independent cohort. The nomogram can be generalized to patients undergoing surgery for RPS by specialized sarcoma surgeons at sarcoma centers. The nomogram provides a more individualized and disease-relevant estimation of OS compared with the American Joint Committee on Cancer classification.
Gesehen am 14.05.2019